2022
DOI: 10.1002/joc.7569
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical synchronization of extreme rainfall events in southwest China

Abstract: Based on the complex network method, this study reveals the temporal and spatial characteristics of the synchronization of extreme rainfall events in southwest China (SWC) during the main rainfall season (May–September). Our results show the significant synchronization pattern of extreme rainfall events in SWC, which is closely associated with the convergence of warm‐wet air and cold‐dry air and the corresponding occurrence of extreme rainfall in SWC. The network divergence indicates a dominated direction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The formation of a PERPE is the result of the combined effect of dynamic and thermodynamic drivers. Many studies have conducted in‐depth research on the mechanism of PERPE processes in SWC (Wang and Tan, 2014; Cheng et al ., 2016; Feng et al ., 2016; Zhang et al ., 2019; Hu et al ., 2021; Xia et al ., 2021; Qiao et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of a PERPE is the result of the combined effect of dynamic and thermodynamic drivers. Many studies have conducted in‐depth research on the mechanism of PERPE processes in SWC (Wang and Tan, 2014; Cheng et al ., 2016; Feng et al ., 2016; Zhang et al ., 2019; Hu et al ., 2021; Xia et al ., 2021; Qiao et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The persistent rainstorm process in the southwest of Yunnan Province might have been affected by the steep terrain and the ample supply of transported water vapour (He et al, 2016). Additionally, Qiao et al (2022) also found that synchronization of the direction of extreme rainfall events in SWC has an obvious spatially asymmetrical feature owing to the more frequent and stronger circulation systems moving from the north to the south rather than from the south to the north, and these different circulation systems can cause different evolutions of extreme rainfall synchronization in SWC (Qiao et al, 2022).…”
Section: Interaction Of Topography Mesoscale Weather Systemmentioning
confidence: 99%
“…Topography greatly affects the synoptic‐scale systems, such as the location of South Asia High (SAH), the position of North Pacific Subtropical High (WNPSH), and the formation and intensity of Southwest Vortex (SWV), which control the precipitation extremes over the SCB in summer (J. Li et al., 2021; Q. R. Ma et al., 2022; Ng et al., 2021; Qiao et al., 2022; A. Wu & Li, 2022; Xia et al., 2021; X. Xu et al., 2023; Y. Zhang et al., 2021). The TP acting as the heat source in summer favors the development and maintenance of SAH (Y. Fu et al., 2020; Y. Liu et al., 2020; G. Wu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, topography slows down the movement of MCS and thus lengthens the duration of precipitation (C. H. Huang et al., 2022; Kang et al., 2019; Phadtare, 2018). The enhancement of the boundary layer southwest low‐level jet (LLJ) provides abundant water vapor at night, this is closely related to the complex terrain (Qiao et al., 2022; Shen et al., 2022). However, the physical processes of the terrain effects on the formation and enhancement of extreme precipitation over the SCB are not well revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation